2009
DOI: 10.1007/s11128-009-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

The sudden death of entanglement in constructed Yang–Baxter systems

Abstract: Some Hamiltonians are constructed from the unitaryŘ i,i+1 (θ, ϕ)-matrices, where θ and ϕ are time-independent parameters. We show that the entanglement sudden death (ESD) can happen in these closed Yang-Baxter systems. It is found that the ESD is not only sensitive to the initial condition, but also has a great connection with different Yang-Baxter systems. Especially, we find that the meaningful parameter ϕ has a great influence on ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In this paper, we extend the study of our previous work [42] to tripartite Yang-Baxter systems. The extension to the case of tripartite systems is not trivial due to the higher degree of complexity of the problem and also for the peculiar structure of tripartite entanglement.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this paper, we extend the study of our previous work [42] to tripartite Yang-Baxter systems. The extension to the case of tripartite systems is not trivial due to the higher degree of complexity of the problem and also for the peculiar structure of tripartite entanglement.…”
Section: Discussionmentioning
confidence: 66%
“…we have also investigated bipartite Entanglement sudden death in constructed Yang-Baxter systems in another paper [42]. In this paper, We mainly explore tripartite Entanglement sudden death in Yang-Baxter systems where we take the unitary Yang-Baxter matrixȒ(θ, ϕ) as the evolution operator U (t) directly.…”
Section: Introductionmentioning
confidence: 99%
“…It is convenient to choose the initial state ρ 0 = 1−γ 4 + γ|ψ ψ| (0 < γ ≤ 1) with |ψ =sinα|01 + cosα|10 . It is worth to mention that in our paper [29], it has been shown that in Yang-Baxter systems, the ESD is not only sensitive to the initial condition , but also has relations with the different Yang-Baxter systems. And it has been found that the meaningful parameter ϕ has a great influence on the ESD.…”
Section: Esd In the Same Yang-baxter Systemmentioning
confidence: 75%
“…Consider a system of two spin-1/2 particles (particle 1 and 2) or nearest spin-spin interaction described by an initial Hamiltonian H 0 [47,61]…”
Section: Dynamical Modelsmentioning
confidence: 99%
“…In another study, it is found that any pure two-qudit entangled state can be achieved by a universal Yang-Baxter matrix (YBM) which satisfies the (universal) quantum Yang-Baxter equation assisted by local unitary transformations [41]. In recent work, the sudden death of entanglement has been investigated in constructed Yang-Baxter systems (YBSs) [47] which are the various extensions of the YBEs for several matrices [48][49][50].…”
Section: Introductionmentioning
confidence: 99%